2000
DOI: 10.1093/toxsci/57.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Hybrid CFD-PBPK Nasal Dosimetry Model in an Inhalation Risk Assessment: An Example with Acrylic Acid

Abstract: The available inhalation toxicity information for acrylic acid (AA) suggests that lesions to the nasal cavity, specifically olfactory degeneration, are the most sensitive end point for developing a reference concentration (RfC). Advances in physiologically based pharmacokinetic (PBPK) modeling, specifically the incorporation of computational fluid dynamic (CFD) models, now make it possible to estimate the flux of inhaled chemicals within the nasal cavity of experimental species, specifically rats. The focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…nasal and laryngeal cavities). Although a complete anatomical model of the ET region of the mouse is not available, limited quantitative morphometric data have been reported and/or estimated for different areas of the URT (Gross et al, 1982;Andersen et al, 2000), as shown in Table 2.…”
Section: Et Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…nasal and laryngeal cavities). Although a complete anatomical model of the ET region of the mouse is not available, limited quantitative morphometric data have been reported and/or estimated for different areas of the URT (Gross et al, 1982;Andersen et al, 2000), as shown in Table 2.…”
Section: Et Regionmentioning
confidence: 99%
“…Additional quantitative data on the mouse nasal cavity in Table 2 have been taken from other independent studies (e.g. Andersen et al, 2000).…”
Section: Et Regionmentioning
confidence: 99%
“…A tool that is increasingly used to assess the respiratory function is computational fluid dynamics or CFD. This method is capable of simulating flow behavior in virtual models (Bush et al, 1998;Andersen et al, 2000;Minard et al, 2006). The challenge is to develop mathematical models that realistically reflect the respiratory physiology of the animal by accurately simulating its fluid flow conditions.…”
mentioning
confidence: 99%
“…The recent RfC documentation for VC in IRIS (US EPA, 2000a) specifically describes and uses a PBPK/PT model for standard setting and dose route extrapolations. A recent risk assessment with acrylic acid (Andersen et al, 2000) applies a PBPK model linked to computational fluid dynamic calculations of nasal airflow (Frederick et al, 1998) to derive an RfC for this compound. The Hazardous Air Pollutants Test Rule (Federal Register, 1996) invited increased efficiency/efficacy in testing by providing possible substitution of certain oral toxicity tests instead of requiring new inhalation studies, for those instances where a validated PBPK model is available to conduct extrapolations across dose-routes.…”
Section: Discussionmentioning
confidence: 99%